Introduction to the Concept of Intercultural Communication (Eurasian Journal of Learning and Academic Teaching, 2023)
In the 21st century, there are fields of linguistics that study language not only as a tool of communication and the result of thinking, but as a cultural opener of the nation. V. Humboldt, A.A. The foundation stone was laid in the scientific work of Potebnya and other scientists. For example, V. Humboldt said that the limits of my nation's language define the limits of my worldview. Language not only reflects existence, but also transforms the existence and environment in which a person lives into his consciousness. Because of this, in the next millennium, Western philosophy is developing based on the process of using language. A. M.